Copper‐Catalyzed Hydrodefluorination of Fluoroarenes by Copper Hydride Intermediates1. Issue 11 (10th February 2013) - Lv, Hongbin; Cai, Yuan‐Bo; Zhang, Jun‐Long
<x xml:space="preserve">Abstract</x> Breaking bad: Efficient copper‐catalyzed CF bond activation has been achieved by replacing fluorine with hydrogen. A copper hydride is proposed as the active intermediate, which proceeds through a nucleophilic attack on the fluorocarbon, as determined by experimental and theoretical results (see structure; C gray, H white, Cu light red, F light blue; distances in Å).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>